(untitled) (International relations and international law Journal, 2016)
This article describes the main theoretical aspects of market and methods of its research. Also, in terms of marketing market research the main problems and their solution by creating a systematic approach to the control of the statistical component of the market situation. The paper in this case is offered governance analysis bases on the state of the market data products and services at the level of macro and microeconomics. SSM – statistical monitoring system proposed analytical work for a more adequate and realistic assessments of comparative market analysis and decision-making at various levels of government. This article includes the main issues conjunctures-structural analysis of the commodity market in marketing, and justified the need for a system of statistical monitoring of market conditions. In conclusion, defines the role and place of the proposed system in a cyclical market analysis.